50 picoarcsec astrometry of pulsar emission - Pen, U-l; Macquart, Jean-Pierre; Deller, A; Brisken, W. (Wiley-Blackwell Publishing Ltd., 2014)
We use very long baseline interferometry (VLBI) imaging of the interstellar scattering speckle pattern associated with the pulsar PSR 0834+06 to measure the astrometric motion of its emission. The D ~ 5 au interstellar baselines, provided by interference between speckles spanning the scattering disc, enable us to detect motions with subnanoarcsecond accuracy. We measure a small pulse deflection of ~18 ± 2 km (not including geometric uncertainties), which is 100 times smaller than the characteristic resolution (λ/D) of this interstellar interferometer. This implies that the emission region is small, and at an altitude of a few hundred km, with the exact value depending on field geometry. This is substantially closer to the star than to the light cylinder. Future VLBI measurements can improve on this finding. This new regime of ultraprecise astrometry may enable precision parallax distance determination of pulsar binary displacements.